Subjective crime of endangering the safety of publictransportation - PhD. professor Bssier Ali Muhammad; Master's student: Ali Muhammad Khudair (The college of law and political science journal, 2024)
The technical progress in public transportation was accompanied by the emergence of a new type of crime distinguished by specific characteristics and marked by a high level of danger and precision in organization. This progress facilitated their commission and led to an increase in the severity of the consequences resulting from acts endangering the safety of these means and their users. Consequently, modern criminal policy has sought to criminalize behavior that would expose the safety of public transportation to harm, as well as behavior that may expose it to danger. Moreover, The legislator has also recently issued instructions that include the necessity of following certain security, and this criminalization is one of the late Abstract danger ,st punitive thought.